Impact of textural patterns on modeled rock weathering rates and size distribution of weathered grains. Issue 6 (2nd March 2021) - Israeli, Yoni; Salhov, Eyal; Emmanuel, Simon
Abstract: Rock texture has a critical influence on the way rocks weather. The most important textural factors affecting weathering are grain size and the presence of cracks and stylolites. These discontinuities operate as planes of mechanical weakness at which chemical weathering is enhanced. However, it is unclear how different rock textures impact weathering rates and the size of weathered grains. Here, we use a numerical model to simulate weathering of rocks possessing grain boundaries, cracks, and stylolites. We ran simulations with either synthetic or natural patterns of discontinuities. We found that for all patterns, weathering rates increase with discontinuity density. When the density was <~25%, the weathering rate of synthetic patterns followed the order: grid > honeycomb > Voronoi > brick wall. For higher values, all weathering rates were similar. We also found that weathering rates decreased as the tortuosity of the pattern increased. Moreover, we show that textural patterns strongly impact the size distributions of detached grains. Rocks with an initial monomodal grain size distribution produce weathered fragments that are normally distributed. In contrast, rocks with an initial log‐normal size distribution produce weathered grains that are log‐normally distributed. For the natural patterns, weathering produced lower modality distributions. Abstract : Numerical model simulating chemical weathering and grain detachment in rocks with different textural patterns. Weathering rate increases with increasing density of discontinuities. Mean size of detached fragments decreases with increasing tortuosity of the textural patterns.